Neural Mechanisms of Sensitivity to Peer Information in Young Adult Cannabis Users - Gilman, Jodi M. (Cogn Affect Behav Neurosci, 2016)
Though social influence is a critical factor in the initiation and maintenance of marijuana use, neural correlates of influence in those who use marijuana are unknown. In this study, marijuana-using young adults (MJ) (n = 20) and controls (CON) (n = 23) performed a decision-making task in which they made a perceptual choice after viewing the choices of unknown peers via photographs, while they underwent functional magnetic resonance imaging scans. MJ and CON did not show differences in the overall number of choices that agreed vs. opposed group influence, but only the MJ group showed reaction time slowing when deciding against group choices. Reaction time was associated with greater activation of frontal regions. MJ compared to CON showed significantly greater activation in the caudate when presented with peer information. Across groups, caudate activation was associated with self-reported susceptibility to influence. These findings indicate that young adults who use MJ may exhibit increased effort when confronted with opposing peer influence, as well as exhibit greater responsivity of the caudate to social information. These results not only better define the neural basis of social decisions, but also suggest that marijuana use is associated with exaggerated neural activity during decision-making that involves social information.